O retorno das danças sagradas : subjetividades espaço-temporais nas sociedades pós-modernas - Barella, Natália Eilert (My University, 2022)
This dissertation addresses the return of Sacred Circle Dances in the so- called post-modern societies. Through a bibliographical research centered in the symbolic aspects of Time and Space, this work intends to understand in which ways this kind of collective manifestation might be a counterpoint to emerging issues in these societies which are scarred by individualism, acceleration and an environmental crisis, amongst other problems. The methodology, which proposes a research "with dance" not only "about dance", includes ego-documents with the intention of constituting a corpus centered in the authors experiences in these practices. The theoretical references are based, especially, on studies of the imaginary and on the work of thinkers from indigenous peoples. [resumo fornecido pelo autor]
A presente dissertação aborda o retorno das Danças Circulares Sagradas nas chamadas sociedades pós-modernas. A partir de uma revisão bibliográfica centrada em aspectos simbólicos do Tempo e do Espaço, procura entender de que forma esse tipo de manifestação coletiva pode ser um contraponto a questões emergentes nessas sociedades, marcadas pelo individualismo, a aceleração e a crise ambiental, entre outros problemas. A metodologia, que propõe uma pesquisa "com dança" e não apenas "sobre dança", inclui, ainda, os egodocumentos, a fim de constituir um corpus centrado nas vivências da autora nessas práticas. O referencial teórico tem por base, especialmente, as ciências do imaginário e pensadores dos povos originários. [resumo fornecido pelo autor]
Keywords: Dança; Dança - Aspectos antropológicos; Simbolismo; Espaço e tempo; Hereditariedade; Dance; Dance - Anthropological aspects; Symbolism; Space and time; Heredity